Implementation of Religious Education in Increasing Children's Interest in Learning in the Era of Digitalization in the Community of Ulujami Village, South Jakarta - idham; Nashiruddin Cholid; Engga Jalaludin; Cucu Cahyati (Jurnal Pengabdian Masyarakat (Bisma), 2023)
Abstract KKN community service activities in educational work programs aim to increase children’s interest in learning in the digital era, where technology has greatly influenced children in their education, both positively and negatively. In addition, the purpose of this service is to provide understanding to the community that the importance of education is to assist the government in educating the nation’s children. This service is carried out through socializing activities directly to the local community about the importance of education for the future of children so that in this way parents also participate in directing, supervising and supporting their children in pursuing education in today’s digital era, in addition we also socialize to The TPQ Al-Bayt Aljamil Foundation by inviting the children to take part in free tutoring with KKN students that we conducted at the post (Al-Bayt Aljamil secretariat field).